Proportion of resected seizure onset zone contacts in pediatric stereo-EEG-guided resective surgery does not correlate with outcome. (June 2022) - Khan, Mehdi; Chari, Aswin; Seunarine, Kiran; Eltze, Christin; Moeller, Friederike; D'Arco, Felice; Thornton, Rachel; Das, Krishna; Boyd, Stewart; Helen Cross, J.; Zubair Tahir, M.; Tisdall, Martin M.
Highlights: Predictors of seizure freedom in children undergoing SEEG-guided resective epilepsy surgery are unknown. It is unknown if complete resection of SEEG-defined putative seizure onset zone contacts is a requirement for seizure freedom. In this study, complete resection of SEEG-defined putative seizure onset zone contacts did not associate with seizure freedom. Abstract: Objective: We aimed to determine whether the proportion of putative seizure onset zone (SOZ) contacts resected associates with seizure outcome in a cohort of children undergoing stereoelectroencephalography (SEEG)-guided resective epilepsy surgery. Methods: Patients who underwent SEEG-guided resective surgery over a six-year period were included. The proportion of SOZ contacts resected was determined by co-registration of pre- and post-operative imaging. Outcome was classified as seizure free (SF, Engel class I) or not seizure-free (NSF, Engel class II-IV) at last clinical follow-up. Results: Twenty-nine patients underwent resection of whom 22 had sufficient imaging data for analysis (median age at surgery of 10 years, range 5–18). Fifteen (68.2%) were SF at median follow-up of 19.5 months (range 12–46). On univariate analysis, histopathology, was the only significant factor associated with SF (p < 0.05). The percentage of defined SOZ contacts resected ranged from 25-100% and was not associated with SF (p = 0.89). In a binary logistic regression model, it was highly likely that histology was the only independent predictor of outcome. Conclusions: The percentage of SOZ contacts resected was not associated with SF in children undergoing SEEG-guided resective epilepsy surgery. Significance: Factors such as spatial organisation of the epileptogenic zone, neurophysiological biomarkers and the prospective identification of pathological tissue may therefore play an important role.